Hydrodynamic modelling of Sungai Skudai/ Zulkifli Ab. Halim - Ab. Halim, Zulkifli (1998)
The aim of the study is to obtain the hydrodynamic characteristic of the Sungai Skudai. It will assist in assessing the impact of development along the downstream stretch of the river. With a knowledge of the existing water levels, velocity and discharge along any cross section of the river the Mike21 modeling software is able to predict future changes in its flow. The objective of the modeling is to simulate flow patterns in the specified area during one tidal cycle with the inputs of water levels at all open boundaries and consequently the model is able to produce a variation of levels and velocities with time at any position within the boundaries. The data collected from field observation were used to further calibrate and verify this model to ensure it is predicting the existing conditions accurately.